Experimental Investigation of Cooling Performance in Automotive Radiator using Al2O3-TiO2-SiO2 Nanofluids - Wan Hamzah Azmi; Rizalman Mamat; Ery Diniardi; Tri Yuni Hendrawati; Anwar Ilmar Ramadhan (Universitas Muhammadiyah Magelang, 2022)
The use of nanoparticle coolant fluid in the car radiator increases the rate of heat transfer and facilitates the reduction of the overall radiator size. In this study, heat transfer characteristics of tri-hybrid nanofluids-based water/EG (60:40) were analyzed experimental and compared with water/EG (60:40). Four different nanofluids concentrations were prepared by adding 0.05 to 0.3 vol.% of tri-hybrid nanofluids dispersed a mixture of water/ethylene glycol (60:40). Experiments were carried out by varying the flow rate of coolant between 2 to 12 LPM for working temperature of 70 Â°C, the velocity of airflow remained at an average of 4 m/s, to understand the effect of coolant flow rate on heat transfer. The results showed that the thermal performance of tri-hybrid nanofluids in a water/EG (60:40) mixture has been investigated for volume concentrations of up to 0.3% and working temperature of 70 Â°C. The maximum enhancement of heat transfer coefficient for air side is observed up to 23.8% at 0.05% volume concentration meanwhile for coolant side is observed at 39.7% at 0.3% volume concentration. The pressure drop and pumping power have the same pattern which increasing in volume concentrations.